Loss of heterozygosity and human telomerase reverse transcriptase (hTERT) expression in bronchial mucosa of heavy smokers - Čapková, Linda; Kalinová, Markéta; Krsková, Lenka; Nováková Kodetová, Daniela; Petřík, František; Trefný, Martin; Musil, Jaromír; Kodet, Roman (Cancer, 2007)
BACKGROUND: Lung carcinogenesis is a multistep process of accumulation of genetic changes, including loss of heterozygosity (LOH), and precedes phenotypic transformation of the bronchial mucosa. The activity of telomerase, correlating with the hTERT mRNA expression, is detectable in a majority of neoplasms. In this study, the frequency of LOH and hTERT expression in bronchial mucosa of heavy smokers in bronchoscopic biopsies was analyzed. METHODS: LOH was examined in 122 bronchial specimens from 81 smokers (67 normal mucosa/bronchitis, 12 squamous metaplasia, 28 dysplasia, 15 bronchogenic carcinoma specimens) by polymerase chain reaction (PCR) and capillary electrophoresis by using 7 fluorescence-labeled markers matching 5 chromosomal regions. hTERT expression was analyzed in 87 specimens (45 normal mucosa/bronchitis, 12 squamous metaplasia, 18 dysplasia, 12 bronchogenic carcinoma specimens) by real-time quantitative reverse-transcription PCR. RESULTS: LOH was detected in at least 1 chromosomal region in 51 of 122 (41.8%) specimens; the incidence in normal bronchial mucosa and preneoplastic lesions was similar (20%-40%); a substantial rise (87%) occurred in carcinomas. The median normalized hTERT(N) values were 6.67 in normal epithelium/chronic bronchitis, 18.38 in squamous metaplasia, 13.31 in epithelial dysplasia, and 75.46 in carcinomas. These results were significantly different (P=.0036). With an increasing number of LOH, the median value of hTERT(N) expression rose, but hTERT was expressed also in tissue samples without any LOH detection. CONCLUSIONS: Results indicated that hTERT expression, together with LOH, represent early events in lung carcinogenesis, as both were detected in precancerous lesions and in normal epithelium of heavy smokers.
Keywords: polymerázová řetězová reakce s reverzní transkripcí; bronchogenní karcinom; Male; Lung Neoplasms; metaplazie; lidé; Bronchi; sliznice; Humans; Smoking; epitelové buňky; prekancerózy; Financing, Organized; Carcinoma, Bronchogenic; Epithelial Cells; Loss of Heterozygosity; Telomerase; bronchy; nádory plic; mužské pohlaví; Reverse Transcriptase Polymerase Chain Reaction; financování organizované; Precancerous Conditions; telomerasa; Mucous Membrane; Metaplasia; messenger RNA; ženské pohlaví; ztráta heterozygozity; Female; kouření; RNA, Messenger